2022
DOI: 10.1021/acsami.2c09555
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Scaling Effects in the Speed of Catalytic Enzyme Micropumps

Abstract: Self-powered, biocompatible pumps in the nanometer to micron length scale have the potential to enable technology in several fields, including chemical analysis and medical diagnostics. Chemically powered, catalytic micropumps have been developed but are not able to function well in biocompatible environments due to their intolerance of salt solutions and the use of toxic fuels. In contrast, enzymatically powered catalytic pumps offer good biocompatibility, selectivity, and scalability, but their performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…where 𝑝𝑝, 𝐈𝐈, 𝜇𝜇, T, and ∇ are the respective pressure, unit tensor, 20,29 fluid dynamic viscosity, temperature, and spatial gradient operator, respectively. 𝜌𝜌 is the real-time fluid density and 𝐮𝐮 is the fluid velocity.…”
Section: Numeric Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…where 𝑝𝑝, 𝐈𝐈, 𝜇𝜇, T, and ∇ are the respective pressure, unit tensor, 20,29 fluid dynamic viscosity, temperature, and spatial gradient operator, respectively. 𝜌𝜌 is the real-time fluid density and 𝐮𝐮 is the fluid velocity.…”
Section: Numeric Simulationmentioning
confidence: 99%
“…If the molecular volume of the reactants and the products of the reaction are different, then the system will generate local density gradients, which give rise to forces that induce fluid motion in the system. [18][19][20] If the products are denser (occupy less volume) than the reactants and the enzyme-attached patch is located on the top wall of the fluid-filled chamber, then the dense, product-laden fluid at the patch initially moves downward and forms convective rolls that circulate towards the patch on the top (as indicated by the direction of the arrows in Fig. 1C).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a micromotor is also a moving pump. , Note that, in addition to the flows generated by the motion itself, a micromotor can significantly change the density of its surrounding liquid as a result of an endo- or exothermic reaction or from the accumulation or consumption of heavy/light molecules. Such buoyancy-induced convective flows have been well documented for catalytic and electrical micropumps (that are fixed in space), but often wrongly neglected for moving micromotors.…”
Section: Interactions Between Chemically Powered Micromotorsmentioning
confidence: 99%
“…[17,18] Earlier analytical models showed that the pumping speed increased with the height of the chamber as h 3 , [8,16] suggesting amplification of the pumping speed in taller chambers. Experimentally, Gao et al [19] recently reported scaling effects in urease pumps and found that larger areas (5 mm in diameter) of the enzyme coating will lead to faster fluid speed in micro-chambers.…”
Section: Introductionmentioning
confidence: 99%